Bioremediation of raw palm oil mill effluent using mix microalgae in Malaysia - Alwan, Inas Jasim (2016)
Palm oil industry in Malaysia is one of the key players in the contribution to the economy of the country. Nonetheless, it also produces a massive amount of palm oil mill effluent (POME). It has been known that microalgae, the unicellular photosynthetic microorganisms possess the ability to reduce the number of pollutants of organic waste. Therefore, this study aims to grow mixed microalgae cultured in different concentrations of raw POME (0.5, 1, 1.5 and 2) % v/v as a biological treatment. This study is conducted on open pond cultivation system (glass tanks) in outdoor conditions. First, it is necessary to allow the mixed microalgae make an adaptation in the raw POME before the start of the actual experiment. The results showed positive effects on the biomass growth of mixed microalgae cultured in the concentration of 1% v/v raw POME. The concentration 1% v/v recorded productivity 0.09 ± 0.02 g/L. day, which significantly higher p < 0.05 compared with the controls and other concentrations. The findings showed that the mixed microalgae could reduce BOD, TN and TP to 78.79, 2.176, and 1.591 respectively. Finally, as many as 10 species of mixed microalgae have been identified from all the experiments, namely Dictyosphaerium sp., Scendesmus sp., Oocystis sp., Monoraphidium sp., Nostoc sp., Cosmarium sp., Aulacoseira sp., Crucigenia sp., Cyclotella sp., and Asterococcus sp.. Since, it is proven that the mixed microalgae able to grow in raw POME, it can be concluded that raw POME is a suitable medium for the cultivation of mixed microalgae without adverse effects.